2022
DOI: 10.31234/osf.io/ukw8t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An SEM Approach to Validating the Psychological Model of Musical Groove

Abstract: The experience of wanting to move in response to music is commonly known as feeling the groove. According to the psychological model of musical groove by Senn et al. (2019), the causes for the urge to move are linked to the properties of the music itself, to the personal background of the listener, to the listening situation, and to feedback loops between body movement and cognition. The model formulates eight hypotheses stating that the music affects a listener’s urge to move mediated through a variety of cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…In their development of the EGQ, Senn et al (2020) proposed a separation of Pleasure and Urge to Move in modeling groove experience and also argued that the latent variable Pleasure might be a precondition to the experience of Urge to Move. Senn et al (2022) confirmed that Pleasure and the Urge to Move are positively associated but also pointed out that it cannot be a strict precondition, since some songs are rated low on Pleasure but high on Urge to Move. Additionally, Düvel et al (2021) point out that Pleasure (as a latent variable measuring the experience of groove) is hard to separate from the construct of simply liking the music.…”
Section: Discussionmentioning
confidence: 53%
“…In their development of the EGQ, Senn et al (2020) proposed a separation of Pleasure and Urge to Move in modeling groove experience and also argued that the latent variable Pleasure might be a precondition to the experience of Urge to Move. Senn et al (2022) confirmed that Pleasure and the Urge to Move are positively associated but also pointed out that it cannot be a strict precondition, since some songs are rated low on Pleasure but high on Urge to Move. Additionally, Düvel et al (2021) point out that Pleasure (as a latent variable measuring the experience of groove) is hard to separate from the construct of simply liking the music.…”
Section: Discussionmentioning
confidence: 53%
“…This might also be related to why people embody music in various ways during spontaneous dance (Toiviainen & Carlson, 2022; Toiviainen et al, 2010). Therefore, we might suggest that groove is not necessarily limited to a typical tempo nor solely to experiences of pleasure and an urge to move, but instead to a combination of several factors (similarly as suggested with the groove model: Senn et al, 2019, 2023). Thus, it is clear that more research investigating different kinds of groove experiences is needed.…”
Section: Resultsmentioning
confidence: 93%
“…Although previous groove models consider the influence of personal background and concrete listening situation for groove experience (Senn et al, 2019, 2023), current mood of the listeners is a rather novel finding in the groove literature. Its contribution requires further investigation and might shed light on the personal and interindividual variance in experience of groove.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When listening to rhythmic music, we often feel an automatic and pleasurable urge to tap our feet or bob our heads along with the underlying beat or pulse of the rhythm. This pleasurable urge to move to music (PLUMM) is a key component of groove (Câmara & Danielsen, 2018;Duman et al, 2022;Janata et al, 2012;Madison, 2006;Senn et al, 2019;Witek et al, 2014) and highlights the deep connection between music, movement and pleasure. In a recent neuroimaging study, we showed that PLUMM is associated with greater activity in dorsal and ventral striatal regions within the basal ganglia (BG), along with cortical regions associated with the motor and limbic cortico-striato-thalamo-cortical circuits (Alexander et al, 1986;Matthews et al, 2020) (henceforth, cortico-striatal circuits).…”
Section: Introductionmentioning
confidence: 99%